Thermal Process Technology Transfer of Masak Habang Snakehead Fish in Poklahsar, Lepasan Village, Barito Kuala: Transfer Teknologi Proses termal Ikan Gabus Masak Habang Di Poklahsar Desa Lepasan Barito Kuala - Rita Khairina; Dewi Kartika Sari; Yuspihana Fitrial; Iin Khusnul Khotimah (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Transfer of thermal process technology for processing masak habang snakehead fish using retort pouch packaging can extend the shelf life of the product to more than 6 months. Masak Habang snakehead fish can be used as an icon of culinary tourism or a typical souvenir product of South Kalimantan. One of the Poklahsar engaged in the processing of fishery products is Poklahsar Berkat Usaha located in Lepasan Village, Bakumpai District. The objectives of this community service activity are 1) to increase the knowledge of Poklahsar Berkat Usaha members about thermal process technology, 2) to provide motivation for diversification and development of fishery products in the form of Masak Habang Snakehead Fish. The activities are carried out in the form of meetings, presentation of extension materials, and demonstrations of product processing. The stages of processing masak habang snakehead fish using thermal process technology are a) preparation of habang spices, b) preparation of snakehead fish, c) product packaging, and d) sterilization process of bottling and retort pouch packaging products. Participation and acceptance of community service activity participants are quite high. The conclusion of the community service activities is expected to open up new business opportunities for Poklahsar Berkat Usaha to produce processed fish by applying thermal process technology, namely Masak Habang Snakehead Fish in glass bottles or retort pouches.